HERPES GESTATIONIS. - Ivelina Yordanova; Valentin Valtchev; Kossara Drenovska; Dimitar K. Gospodinov; Snejina Vassileva (Peytchinski Publishing, 2014)
Herpes gestationis, also known as pemphigoidgestationis (PG) is an extremely rare autoimmune bullous dermatosis of the gestation and postpartum period. The disease was originally named herpes gestationis on the basis of the morphological herpetiform feature of the blisters. We report a 21-year-old woman, pregnant in the third trimester, who presented with a pruritic bullous cutaneous eruption of two weeks duration. The disease started with a red plaque in the abdominal area accompanied by mild itching. Soonafter, blisters appeared and affected almost the entire body. Physical examination revealed a primiparous woman in good general state, pregnant in 36 weeks of gestation. The skin changes affected the abdomen, back of the trunk, upper and lower extremities, hands and feet. They were manifested by a polymorphous eruption, consisting of erythematous urticaria-like plaques, small tense vesicles and multiple excoriations. Mucous membranes were not affected. Routine laboratory examinations were within normal limits. Direct immunofluorescence (DIF) on perilesional skin showed linear deposition of IgG (++) and C3 (++) at the cutaneous basement membrane zone (BMZ). Indirect immunofluorescence (IIF) on human esophagus substrate revealed circulating IgG anti-BMZ antibodies at a titer of 1:80. ELISABP180 NC16A was strongly positive. The diagnosis of PG was confirmed and a treatment with systemic methylprednisolone 60 mg/day was initiated, later gradually tapered to 20 mg/day, together with topical corticosteroids. As a result on the 10th day of the treatment we already achieved significant improvement with reduction of erythema and itching, absence of new skin lesions. The pregnancy ended in term with successful childbirth. No flare of the skin disease was observed in the puerperal period.